Impact of addition of ca on clogging of SEN and magnetic properties of non-oriented silicon steel - Kong W.; Cang D.G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The submerged entry nozzle (SEN) clogging has been happening during continuous casting (or CC for short) for nonoriented silicon steel. To solve the problem, the paper studied a flow rate through SEN, a node attached to one of them, and the impact on the clogging. The results showed that when SEN is clogged seriously, the casting speed has to decrease below the target casting speed and that SEN clogging can be predicted by comparing the actual value and the theoretical one of a casting speed. Al2O3 and its composite inclusions caused the SEN clogging and the addition of Ca can solve SEN clogging during CC of the silicon steel both theoretically and practically. Furthermore, the impact of the addition of Ca on the magnetic properties of the steel were analyzed. The results showed that the core loss and the magnetic induction of the silicon steel decreased by using the addition of Ca, which generated more dissolved Aluminum, and the addition of Ca generated more harmful textures, which reduced the magnetic induction.